PENGARUH VARIASI SUDUT POTONG MAYOR TERHADAP KEKASARAN PERMUKAAN HASIL PROSES PEMBUBUTAN MUKA ALUMINIUM SILICON (Si) DAUR ULANG - Isyrouddin, Faishol Aziz Isyrouddin Aziz; Sumbodo, Wirawan (Journal of Mechanical Engineering Learning, 2020)
Non-conventional machining technology becomes a solution to reduce the inefficiency of production time and is required when conventional machines are deemed unable to work on a workpiece with complex and very detailed contours. In the process of machining requires a chisel that works as a means of cutting workpiece. The quality of the lathe can be viewed in many ways including the smoothness of the workpiece surface roughness. Variation of major side edge cutting angle on HSS cutting tool used in this study was 75 °, 77 ° and 80 °. While the dependent variable to be studied is surface roughness. Method of data processing is done by descriptive analysis. The results showed that the larger cutting angle and larger spindle rotation resulted in lower surface roughness. The highest arithmetic mean roughness (Ra) value of 10.782 μm is generated from the major side edgecutting-edge parameters of 75 °, and 293 rpm rotation. While the parameters of cutting angle major 80 °, and round 1480 rpm obtained the lowest surface arithmetic mean value (Ra) of 5.361 μm.